2018
DOI: 10.1016/j.adro.2018.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Salvage reirradiation for local failure of prostate cancer after curative radiation therapy: Association of rectal toxicity with dose distribution and normal-tissue complication probability models

Abstract: PurposeThis study aimed to assess the impact of radiation dose on rectal toxicity after salvage external beam radiation therapy (EBRT) with or without a brachytherapy boost for exclusive local failures after the primary EBRT for prostate cancer.Methods and materialsFourteen patients with no severe residual late toxicity after primary EBRT ± brachytherapy were reirradiated after a median time interval of 6.1 years. The median normalized total dose in 2 Gy fractions (NTD2Gy, α/β ratio = 1.5 Gy for prostate cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…Studies exploring dose‐volume rectal toxicity during EBRT have found that the risk of developing toxicity increases exponentially with the volume of rectal wall irradiated, with volumes of 1 cc receiving ≥70 Gy significantly increasing the risk of grade 2 or above late toxicity . Our results indicate that 1 cc of the rectal wall would receive 45% more dose than planned when a large unplanned gas cavity is present.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Studies exploring dose‐volume rectal toxicity during EBRT have found that the risk of developing toxicity increases exponentially with the volume of rectal wall irradiated, with volumes of 1 cc receiving ≥70 Gy significantly increasing the risk of grade 2 or above late toxicity . Our results indicate that 1 cc of the rectal wall would receive 45% more dose than planned when a large unplanned gas cavity is present.…”
Section: Discussionmentioning
confidence: 71%
“…Studies exploring dose-volume rectal toxicity during EBRT have found that the risk of developing toxicity increases exponentially with the volume of rectal wall irradiated, with volumes of 1 cc receiving ≥70 Gy significantly increasing the risk of grade 2 or above late toxicity. [25][26][27][28] Our results indicate that 1 cc of the rectal wall would receive 45% more dose than planned when a large unplanned gas cavity is present. As it has been shown that limiting the D 1cc dose constraint to 55 Gy during pancreas chemoradiation reduces grade 2+ duodenal toxicity 47% to 9%, this approach could help to reduce risk of toxicity during MRgRT.…”
Section: A Implications Of Unplanned Gas In the Rectal Wallmentioning
confidence: 70%
“…Only 1 study was prospective, 27 and the remainder were retrospective. Of the 6 articles meeting eligibility criteria but not included in the quantitative analysis, 5 studies contained a major amount of overlap with a larger and more recently published study population, 39 , 40 , 41 , 42 , 43 and 1 study further detailed toxicity of re-RT 44 of an otherwise included study. 28
Figure 1 Preferred reporting items for systematic reviews and meta-analyses diagram of study selection for our systematic review.
…”
Section: Resultsmentioning
confidence: 99%
“…A summary of organs at risk (OAR) constraints used for bladder and rectum is presented in Appendix E4 . Dose-volume histogram information in the cohort published by Zilli was analyzed by Dipasquale et al 44 to predict GI toxicity. This identified increasing cumulative D1cc (minimum dose to 1 cm³ of the most irradiated volume) to the rectum was associated with grade 3/4 GI toxicity, and staying below a combined threshold of 130 Gy (α/β= 3) may be a reasonable target.…”
Section: Resultsmentioning
confidence: 99%
“…For example, in the series presented by Loi et al, 1-year biochemical relapse-free survival was 80%, comparable with 85% 1-year biochemical progression free survival rate in our series when BED ≥130 Gy was administered. Nonetheless, we have to considered that most our patients received a relatively low dose at the first course of RT (median dose of 70.2 Gy), while for patients recently treated in the dose escalation era with higher BED at first treatment, the safe dose of re-EBRT still have to be defined, especially for the risk of late rectal toxicity 47.…”
mentioning
confidence: 99%